Probing the Ph measurement of self-alligned polysilicon nanogap capacitor - Nazwa, Taib; Uda, Hashim, Prof. Dr.; Mohammad Nuzaihan, Md Noor (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/